2016
DOI: 10.1001/jamapsychiatry.2015.2582
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Reward Activity and Antipsychotic-Associated Weight Change in Patients With Schizophrenia Undergoing Initial Treatment

Abstract: IMPORTANCE Weight gain is a common and serious adverse effect of antipsychotic treatment. A variable individual predisposition to development of metabolic disturbances calls for predictive biological markers. OBJECTIVES To investigate whether attenuated striatal activity during reward anticipation is associated with amisulpride-induced weight change in antipsychotic-naive patients with schizophrenia undergoing initial treatment and to examine the association between weight change and changes in reward anticipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 55 publications
2
59
0
Order By: Relevance
“…The only longitudinal study in this area used a MID paradigm to study weight change in patients treated with the highly selective D2-and D3-receptor antagonist amisulpride (Nielsen et al, 2016). Confirming our proposal, a decrease in reward anticipation over the course of 6 weeks predicted greater weight gain.…”
Section: Role Of Medication In Weight Gainsupporting
confidence: 64%
See 3 more Smart Citations
“…The only longitudinal study in this area used a MID paradigm to study weight change in patients treated with the highly selective D2-and D3-receptor antagonist amisulpride (Nielsen et al, 2016). Confirming our proposal, a decrease in reward anticipation over the course of 6 weeks predicted greater weight gain.…”
Section: Role Of Medication In Weight Gainsupporting
confidence: 64%
“…Only one recent longitudinal study looked at the relation between weight gain, striatal activity and antipsychotic treatment in schizophrenia. At follow-up, six weeks after baseline measurement with amisulpride, Nielsen and colleagues (Nielsen et al, 2016) found in N = 39 patients treated with amisulpride that reward anticipatory responses in the MID task were associated with weight gain. Patients with lower baseline reward anticipation in the right putamen showed stronger weight gain.…”
Section: Why Does Weight Gain Not Start Before Pharmaceutical Treatment?mentioning
confidence: 99%
See 2 more Smart Citations
“…As a noninvasive and relatively safe tool for investigating in vivo brain function with high spatial resolution, fMRI can be used to measure the biological effects of candidate treatment strategies, and may provide a useful biomarker in clinical trials (29, 32). The promise of these approaches have been demonstrated in recent work indicating that functional connectivity of the striatum can predict response to APMs in first episode psychosis (33) and that striatal activity during reward anticipation predicts weight gain in response to subsequent APM therapy (34). …”
Section: Introductionmentioning
confidence: 99%